Oil algae extraction from nannochloropsis SP: a study of soxhlet extraction and ultrasonic assisted extraction - Wiyarno, Budi; Yunus, Rosli Mohd; Mel, Maizirwan (2010)
This is a study on oil extraction from microalgae for basic material of biodiesel. It was carried out by sokhlet extraction (SE) and ultrasonic assisted extraction (UAE). While the types of microalgae being studied was Nannochloropsis sp., the solvent used was ethanol. The extraction process was done by varying the ethanol concentration (66%, 70%, 80%, 90% and 94%) and varying the time (80, 100, 150, 200 and 220 minutes). The ratio of microalgae to solvent is 1:3 g/ml. The UAE was run by using ethanol 96%; the ratio of algae to solvent was varied, they are 1:3, 1:5, and 1:10 g/ml; while the temperature differences were 23, 40 and 60 oC and the frequency was 40 kHz. The better quality of algae oil was gained when the ethanol concentration is 70%. The level of Free Fatty Acid (FFA) was 9.4 % and the saponification number was 286.8. Meanwhile, the amount of circulation also influences the quality of oil yield. The amount of optimum circulation is 20 (200 minutes or 3. 3 hours). Given 200 minutes, the better quality of algae oil was gained, i.e. 26% of algae’s weight. Ethanol selectivity increased more as the concentration was raised. To some extent, the increase of concentration will cause the selectivity decrease. The use of ultrasonic in extraction is beneficial as it reduces the use of time and temperature significantly, i.e. it needs only 51.6 minutes in 69.62 o C.